Koreografi Tari Kreasi Bala Anjani - Nahdlatuzzainiyah, Nahdlatuzzainiyah; Yuliatin, Riyana Rizki; Imtihan, Yuspianal; Murcahyanto, Hary (TAMUMATRA, 2021)
This study aims to describe choreography analysis, namely the form of motion, motion techniques and dance style created by Bala Anjani Sanggar Tunggal Galih Denggen Village, Selong District, Lombok Timur Regency. This type of research is descriptive qualitative using analysis of motion forms, motion techniques and motion styles. Data collection techniques in this study use observation techniques, interviews, and documentation. Data validity techniques use triangulation techniques. The results of the analysis of dance choreography created by Bala Anjani obtained that; The form of motion in The Creation of Bala Anjani dance has the Unity Principle of 6 forms of motion which each has elements of space, energy elements and elements of time vary, The principle of variation consisting of variations of movement, tempo of music and floor patterns, Principle of Repetition in each motion is characterized by a different duration of time, the Principle of Displacement is carried out by a pause of movement of one to two seconds to the next movement, the Climax Principle is performed at a fast tempo on the last movement. In Motion Engineering does not have a medium technique but has a complete and different instrument technique on each movement. While in the Style of Motion consists of bejonjong motion that is raised at a high level, Ngampeh motion is flicking with downward and upward movements followed by varied footsteps and ngampet motion that is peeling with fast movements. The conclusion of this study is 1) the form of motion analyzed from the principle of unity between the space forces of time, the principle of variation, the principle of repetition, the principle of displacement and climax; 2) motion techniques are analyzed from; Medium technique and instrument technique 3) motion style consists of Bejonjong motion, Ngampeh motion and Ngampet motion